The Psychology of Panic - Motta, Robert W. (IntechOpen, 2023)
Panic disorder is often confused with elevations of anxiety and what is often described as "anxiety attacks." However, panic is qualitatively different from these phenomena. Panic disorders or panic attacks are intense and usually brief episodes that have often come upon the sufferer as an extreme dread and fear of annihilation. Panic attacks are startling and often produce a sense of impending doom and fear of imminent disaster. They are associated with heart palpitations, dizziness, tingling of extremities, disorientation, and the urge to flee the present environment. During a panic attack, it is not unusual for the sufferer to act in ways that seem completely irrational and beyond the realm of sanity. Imagine sitting quietly in a darkened room and being intensely engrossed in a book that you cannot put down. Suddenly you feel someone's hands grasp your neck and begin choking you. That level of startled and life-threatening fear is like what many report during a panic attack. It is difficult to know what causes this disorder. In many cases, sufferers report having endured traumatic experiences, especially in childhood. However, in an equal percentage of cases, there is no prior trauma history, and the origins of the panic disorder are unknown, although they do tend to run in families. This book elucidates the nature of panic, the factors that contribute to the disorder, and describes psychological, physiological, and medical interventions that have been useful in ameliorating the suffering brought on by panic attacks.